Coming out of the hard of hearing closet: Reflections on a shared journey in academia - Blankmeyer Burke, Teresa; Nicodemus, Brenda (Disability Studies Quarterly, 2013)
Deaf academics who navigate aspects of their professional lives through signed language interpreting services face a range of issues, including handling perceptions of their Hearing peers, identifying and negotiating their own communication preferences, and balancing personal and professional relationships with their interpreters. Interpreters bring individual sets of schemas and skills to their work, which impacts the interpreted interaction. In this paper, a Deaf academic and her interpreter/colleague discuss various challenges in having an interpreter—and being an interpreter—in academia. Topics include being “outed” as a person with a disability because of the presence of an interpreter; the need for interpreters with specialized academic vocabulary; the responsibilities of the Deaf academic and the interpreter in interpreted interactions; and the sense of vulnerability, intimacy, and autonomy experienced by the Deaf academic and the interpreter. The article is a shared reflection about the evolution of a relationship, beginning with the authors’ respective roles as client and interpreter, and leading into to their present alliance as colleagues and friends. Key words: interpretation, Deaf, academic, ethics, disability, autonomy, vulnerability, intimacy, philosophy, hard of hearing, hearing impaired, sign language, oral interpreting, American Sign Language